Perlindungan Hukum bagi Pemegang Sertifikat Hak Milik Atas Tanah dalam Kasus Sengketa Sertifikat Ganda: (Studi Kasus Putusan Ma Nomor 309 Pk/Pdt/2021) - Sabio Astroman Saragih; Rosnidar Sembiring; Henry Sinaga (CV Rewang Rencang, 2025)
Legal protection for landowners holding land title certificates is a fundamental aspect of Indonesia's land system, which is normatively guaranteed through Law concerning Basic Regulations and Government Regulation, The research method employed is normative juridical approach conducted through literature study to obtain secondary data. certificates function as strong evidence. However, in practice, legal uncertainty still exists due to various factors such as land disputes, overlapping certificates, and weak supervision systems in the land registration process. Analysis of Supreme Court Decision Number 309 PK/Pdt/2021 shows that the Panel of Judges reinforces legal protection for certificate holders who registered legitimately and in good faith by applying the principle of registration time priority, where the party who registers first has stronger rights. This decision also affirms the rejection of overlapping certificates containing legal defects to strengthen legal certainty in the land system.